Investigating the Influence of Individual and Organizational Doctors on Job Performance among Nurses in Public Sector Hospitals of Karachi - Tasneem Razzak; Tahira Hamid Ali; Tariq Ahmed Shaikh; Sadaf Badiuzzaman (Research Journal of Psychology, 2024)
Purpose: The aim of this study was to design the model which describes the job performance of nurses based on individual and organizational factors. It shows the causal relationship between four independent variables: occupational stress, turnover intention, supervisor support and working environment, one moderating variable: self-efficacy and one dependent variable: job performance and its impact on job performance. Method: The quantitative approach was adopted for this research study, the convenience sampling technique was used in this study, investigation was administered through a questionnaire considering 300 nurses professionally, employed at Karachi’s renowned tertiary care centers. This questionnaire assessed six distinct variables: job performance, working environment, occupational stress, supervisor support, self-efficacy, and turnover intention. The present study used Smart-PLS 0.4. Results: The results of structural model confirmed that occupational stress negatively affects job performance (β=-0.464 t=6.319<0.05). Turnover intention negatively affects job performance” (β= -0.422 t=5.891<0.05). Supervisor support “positively affects job performance” (β= 0.309 t=2.680, 0.000). And working environment “positively affects job performance” (β= 0.356 t=7.832, 0.000). We found support for all indirect hypothesis except hypothesis 6 (H6) the “moderating effect of self-efficacy on turnover intention and job performance” ((β= -0.208 t=1.258>0.05). Implications for nursing management: To enhance job performance in the nursing department, the management of the care centers can update organizational work practices, modernize policies to create better work-life balance, initiate support from the supervisors, and invest in counselling of the nurses individually.